The effect of resuscitation strategy on the longitudinal immuno-inflammatory response to blunt trauma. Issue 12 (December 2017) - Bonde, Alexander; Nordestgaard, Ask Tybjærg; Kirial, Rasmus; Svenningsen, Peter; Sillesen, Martin
Abstract: Introduction: Resuscitation strategies following blunt trauma have been linked to immuno-inflammatory complications leading to systemic inflammatory syndrome (SIRS), sepsis and multiple organ failure (MOF). The effect of resuscitation strategy on longitudinal inflammation marker trajectories is, however, unknown. We hypothesized that the effect of resuscitation strategy extends beyond the trauma-related coagulopathy, perhaps affecting the longitudinal immuno-inflammatory response to injury. Methods: We analyzed data prospectively collected for the Inflammation and Host Response to Injury (Glue Grant) study. Blood sampling for inflammation marker analyses from blunt trauma patients was done on admission days 0, 1, 4, 7, 14, 21 and 28 where applicable. Total volume transfused of packed red blood cells (PRBC), fresh frozen plasma (FFP), platelets (PLT), and crystalloids during the initial 48 h was extracted, along with an analysis for an array of cytokines by Enzyme Linked Immunosorbent Assay (ELISA) technique. A within patient concentration change (WPCC) was calculated to quantify longitudinal alterations in cytokine levels, while controlling for potential confounders. To account for the multiple comparisons performed, p -values obtained from the multivariate regression model were post-hoc corrected by the false detection rate (FDR) q-value. Results: No longitudinal trajectories of inflammatory markers were found to be associated with PRBC- or PLT transfusion. Three proinflammatory cytokines (Il-1β, MIP-1β, and TNFR2) were negatively associated with volume of FFP transfused (q = 0.02, q < 0.001 and q = 0.007 respectively), and one proinflammatory cytokine (MIP-1β) was positively associated with crystalloid infusion (q = 0.005). Conclusions: Resuscitation strategy employed following blunt trauma has limited association to longitudinal inflammation marker trajectories, with a potential association between the strategy employed and IL-1β, TNFR2, and MIP-1β trajectories, respectively.